Political management of youth students’ electoral participation in Russia: topical issues - E. A. Belikova; E. V. Zlotnikova; V. F. Nitsevich (Управление)
Electoral participation is the most accessible way for citizens to influence the political course of the country. This determines the relevance of the chosen research topic. In the course of the study, the authors found that a set of measures, aimed at changing the order of organization and conduct of voting in Russia, contributed to an increase in the effectiveness of the electoral process and the interest of the youth audience in political activity. The purpose of this study is to identify modern mechanisms of political management of electoral participation of student youth in Russia. The objectives of this study are to study the interest of student youth in the implementation of socio-political activities, as well as to identify the features of electoral behavior of student youth in Russia. The research was conducted using such methods as: classical analysis of documents, the method of comparative analysis and the survey conducted in the form of a questionnaire using the Google.forms resource. The results of the author’s sociological research “Political activity of youth as a factor of electoral participation in Russia” show that students are willingly interested in socio-political activities and express their interest in the development of civic initiative. In the course of the study we found a growing interest among students in a new, for Russia, form of political participation – political volunteering.